2008
DOI: 10.1021/ol8015012
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Addition of Diethylzinc to Trifluoromethyl Ketones

Abstract: A procedure for nucleophilic addition of diethylzinc to trifluoromethyl ketones was developed. The TMEDA-catalyzed method converts aromatic substrates to the corresponding 2-aryl-1,1,1-trifluorobutan-2-ols in up to 99% yield, and it is also applicable to less reactive aliphatic ketones if stoichiometric ligand amounts are employed. The first asymmetric variant producing tertiary alcohols with up to 61% ee when TBOX is used as catalyst is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 46 publications
2
24
1
Order By: Relevance
“…Slightly better results were observed when the more activated ketone 2,2,2-trifluoroacetophenone was employed (showing conversions of 38 % and 46 % to the relevant alkylation and reduction products), which contrasts with the complete lack of alkylation reaction observed when homometallic ZnEt 2 is employed, where after 24 h, the relevant secondary alcohol is obtained in a 74 % yield. [41] Therefore, adding to our previous findings, [13] these results emphasise even more the significant role that inorganic salts such as MgCl 2 or LiCl (which on many occasions are present in solution due to the common use of in situ metathetical approaches) can play in organic synthesis, where far from being mere spectators, they can interact not only with the organic substrate but also with the organometallic species involved.…”
Section: Resultssupporting
confidence: 58%
“…Slightly better results were observed when the more activated ketone 2,2,2-trifluoroacetophenone was employed (showing conversions of 38 % and 46 % to the relevant alkylation and reduction products), which contrasts with the complete lack of alkylation reaction observed when homometallic ZnEt 2 is employed, where after 24 h, the relevant secondary alcohol is obtained in a 74 % yield. [41] Therefore, adding to our previous findings, [13] these results emphasise even more the significant role that inorganic salts such as MgCl 2 or LiCl (which on many occasions are present in solution due to the common use of in situ metathetical approaches) can play in organic synthesis, where far from being mere spectators, they can interact not only with the organic substrate but also with the organometallic species involved.…”
Section: Resultssupporting
confidence: 58%
“…This observation resembles catalytic reactions of aromatic substrates under the action of C2-symmetric chiral catalysts that occur with anomalous low ee, i.e., an almost racemic product. Addition of diethylzinc to trifluoromethyl ketones (aromatic) over С2-symmetric chiral auxiliaries (10) pertains to such reactions (Table 4) [126]. Thus, the deviation from the linearity in favor of the racemic product ((-)-NLE) occurs in case aromatic substrates in reactions catalyzed by homochiral C 2 -symmetric dimeres in situ formed from dialkylzinc.…”
Section: Ohmentioning
confidence: 99%
“…36 However, due to the high reactivity of the diorganomagnesium reagent, a stoichiometric amount of chiral amide ligand and a low temperature (À78°C) were required to achieve high enantioselectivity. Diethylzinc is as a well-known b-hydrogen donor and was used in the reduction of trifluoromethyl ketones by Higashiyama et al 37 some other groups also found that trifluoromethyl ketones could be reduced by diethylzinc, [38][39][40][41] but the asymmetric version of the b-hydrogen transfer reduction of a-trifluoromethyl ketones with diethylzinc has never been reported.…”
Section: Introductionmentioning
confidence: 99%